Salafismus in Deutschland: Ursprünge und Gefahren einer islamisch-fundamentalistischen Bewegung - Schneiders, Thorsten Gerald (transcript, 2014)
Salafism: There is probably no other radical Islamic movement (not only) in Germany that has aroused that much attention in recent years. In spite of their strict religious rules, the fundamentalists can enjoy rather quickly growing numbers. While the number of followers increases, the rest of the population remains increasingly baffled. Who are the Salafists, what do they want, whom are they threatening? This volume gives comprehensive answers to these questions and locates Salafism within Islamic history. It provides impulses for the societal handling of the phenomenon, and gives immediately affected people room to speak about their experience with Salafists.